Performance of Rapeseed Grown Under Different Agronomic Management in Chitwan - Basnet, B.B.; Basnet, K.B.; Yadav, D.N.; Chand, S.P. (Journal of the Institute of Agriculture and Animal Science, 2004)
A field experiment was conducted during the winter season of 2001-2002 at Mangalpur, Chitwan, Nepal to evaluate the performance of rapeseed in different agronomic management practices. The experiment was conducted with 16 treatments in a randomized complete block design (RCBD) with three replications. The treatments included control without input and four agronomic inputs (NPK, FYM, micronutrient- Zn, B and S and weeding), two and three factors combinations of these inputs and a full package with all inputs. Significantly higher plant height was recorded at 55 days after sowing in the combination of all sources of nutrition i.e. NPK fertilizers, FYM and micronutrient. Application of NPK fertilizers (60:40:20 kg/ha) gave significantly higher (490.8 kg/ha) seed yield as compared to control and weeding. The application of NPK fertilizers with FYM @ 12.0 t/ha) produced significantly higher yield (657.4 kg/ha) compared with other two factor combination of FYM and weeding. The highest (800.9 kg/ha) yield was achieved in three factor combination with all sources (NPK, FYM and micronutrient) of nutrients. In general, addition of NPK fertilizers to different inputs assisted to increase rapeseed yield significantly. Moreover, combination of NPK fertilizers with FYM gave comparatively higher benefit cost ratio of 1.56. J. Inst. Agric. Anim. Sci. 25:11-16 2004